NON-LINEAR DYNAMICS OF THE LITHOSPHERE AND INTERMEDIATE-TERM EARTHQUAKE PREDICTION - Keilis-Borok V.; Ismail-Zadeh A.; Kossobokov V.; Shebalin P. (My University, 2001)
The lithosphere of the Earth is structured as a hierarchical system of volumes of different sizes, from about 10 tectonic plates to about 1025 grains of rock. Their relative movement against the forces of friction and cohesion is realized to a large extent through earthquakes. The movement is controlled by a wide variety of independent processes, concentrated in the thin boundary zones between the volumes. The boundary zone has a similar hierarchical structure, consisting of volumes, separated by boundary zones, etc. Altogether, this hierarchy of volumes and multitude of processes compose the lithosphere into a large non-linear complex system. Upon coarse graining the integral mesoscale empirical regularities emerge, indicating a wide range of similarity, collective behavior, and the possibility of earthquake prediction. This approach led to new paradigms in the dynamics of the lithosphere and, on the practical side, created a capacity to predict from 70 to 90% of large earthquakes, with alarms occupying 10–20% of the time–space considered. Such predictions may be used to undertake earthquake preparedness measures, which would prevent a considerable part of the damage (although far from the total damage). The methodology linking prediction with preparedness was developed; it may help a disaster management authority to choose the preparedness measures, allowing for the currently realistic accuracy of predictions. A large-scale experiment in advance prediction of large earthquakes worldwide has been launched to test the prediction algorithms. The test is unprecedented in rigor and coverage. The forecasts are communicated, with due discretion, to several dozen leading scientists and administrators in many countries. Among already predicted earthquakes are all the last eight great ones with magnitude 8 and more. The major drawback is the rate of false alarms. The possibility is outlined to develop a new generation of prediction methods, with fivefold increase in accuracy and the transition to short-term prediction. The links with prediction of geotechnical and engineering disasters are established: scenarios of transitions to a large earthquake happen to share some features with a broader class of catastrophes. This experience now opens as yet untapped possibilities for reduction of technological disasters.
Keywords: seismicity; prediction algorithm; models of lithosphere dynamics; natural disaster reduction